Kajian Pemanfaatan Air Hujan Sebagai Pemenuhan Kebutuhan Air Bersih Di Pulau Kecil Studi Kasus : Desa Concong Tengah Kecamatan Concong Kabupaten Indragiri Hilir - Indah Ameliana Beza; Yohanna Lilis H; Imam Suprayogi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The main purpose of research is to establish the quantitative hydrology individual scale rain water harvesting to meet water needs in the Middle District of Concong Concong village Indragiri Hilir. The method used is by using auxiliary program Rain Cycle 2 were simulated using community input data roof area (m2), the water needs based on the number of family members (m3/day) and daily rainfall data in a single year (mm / year). The main results of the study was to determine the quantitative hydrology rainwater harvesting to meet the needs of clean water for villagers in the Middle District of Concong Concong Indragiri Hilir ie the percentage of the amount of water which water is met for 3 tanks of at least 50% based on the water needs in 2010 through 2014.Keywords : Rain Water Harvesting, Hydrology Quantitative, Rain Cycle 2, Small Island